Bidirectional promoter elements of simian virus 40 are required for efficient replication of the viral DNA. - Hertz, G Z (1986)
Mutants of simian virus 40 (SV40) lacking parts of the 72- and 21-base-pair repeat regions were made deficient in large T antigen by recombination with dlA 4000, a mutant containing a frameshift deletion near the amino terminus of the T antigen genes. These double mutants were transfected into COS cells, and the amounts of replicated viral DNA were measured at various times thereafter. It was found that deletion of either the 72- or 21-base-pair repeat region did not significantly reduce the accumulation of viral DNA. However, cells transfected with mutants lacking both of these promoter elements accumulated 100-fold less viral DNA than cells transfected with wild-type SV40. This indicates that the 72- and 21-base-pair repeat regions are each sufficient for supplying a function required for efficient replication of SV40 DNA. In addition, the ability of either of these regions to support efficient replication was gradually reduced as the number of promoter elements within each was decreased. Since the 72- and 21-base-pair repeat regions bidirectionally induce transcription, our results indicate that bidirectional promoter elements play a role in the replication of viral DNA. However, fewer of these elements are required for efficient replication than for efficient transcription.